ABOUT SOCIO-ECONOMIC FACTORS IN THE DEVELOPMENT OF MODERN RUSSIAN LEGISLATION - Kornev, Arkadiy; Lipen, Sergey; Zenin, Sergey (Revista Inclusiones, 2020)
The article deals with the current development issues of Russian legislation. The authors show the determining role of economic and, more broadly, social factors that determine the law development vector. The study calls into question the idea of the alleged self-sufficiency of a law that develops according to its internal regularities and argues the thesis about the need to study law in the context of cause-and-effect relationships between legal and social factors. The authors use individual particular and special methods, such as sociological, comparative-legal, historical, and logical. An important place is given to the use of systematic and structural-functional approaches, as well as the formal-dogmatic methodology that allows analyzing the quality of normative material. It is concluded that the social significance of the law is manifested in the need to ensure proper socioeconomic dynamics and mobility through constant updating and improvement of legislation. The entire legal system is undergoing significant changes, and the quality of the legal environment and legal education is changing.